Sources of Health Information on COVID-19 and Adherence to Measures to Prevent Community Spread among Rural Dwellers in Rivers State, Nigeria - Ijah, Christiana N.; Adegbite, Stella N. (NIU Journal of Social Sciences; Vol. 9 Núm. 1 (2023): NIU Journal of Social Sciences, Vol. 9 No. 1, March 2023DO - 10.58709/niujss.v9i1.1590, 2023)
This paper examines the source of health information on COVID-19 and the level of adherence to the necessary measures to prevent community spread in rural communities. The study was carried out in five rural communities in Rivers State, South-South Nigeria. Two research questions guided the study. The instrument for data collection was a structured questionnaire tagged “Instrument for Assessing Sources of Health Information on Covid-19 and Adherence to Measures to Prevent Community Spread in Rural Areas (ASHICAMPSRA)”. The data generated were analyzed using descriptive statistics to answer the research questions. Mean and percentages were used to analyze the data. The study reveals that community education centre was the major source of health information on COVID-19, that rural dwellers acquire knowledge on basic health literacy on prevention of community spread of the virus, the symptoms when infected, management of infected persons, and information on vaccination from the community education centre. The study also reveals that rural dwellers adhere to three preventive measures out of seven to a high extent. The preventive measures adhered to highly are: staying home during the lockdown, hand washing and avoiding large gathering. Based on the finding, the conclusion is that there was inadequate use of the old and new media like community radio and community newspaper as well as relative poor adherence to the measures to prevent community spread of the corona virus.  The study provides an insight on sources of health information in COVID-19 in rural communities and the extent of adherences to the preventive measures. These findings can inform tailored community intervention to promote health information on COVID-19. Keywords : Health Information, Rural Dwellers, Community Education, COVID-19 Prevention